Impact on BER of Different Detectors for 2*2 MIMO System under Rayleigh Channel - Vashishth, M; Beniwal, N.S (International Journal of Computer Sciences and Engineering, 2018)
This paper is motivated by the potential of multi input multi output (MIMO) frameworks to accomplish high speed data rate demand of future generation wireless systems because these are capable of mitigating multipath fading effect without increased spectral bandwidth. This paper is generalized to the case of 2 antennas at both sides For separating spatially multiplexed information ZF and MMSE and ML detectors have been used so that goal of information gathering maximizes at receiver end. ZF and MMSE identifiers are used if system complexity is issue or ML is used if BER performance is to be considered. No feedback is required from receiver to transmitter in this methodology. In this paper BER execution of 2*2 MIMO framework with different detectors at the beneficiary side has been evaluated under Rayleigh blurring channel, which is usually a case of no line of sight. These frameworks are implemented by using MATLAB, which gives us performance comparison between 2*2 MIMO framework with different detectors and classical maximal ratio combining scheme.